Modified Six Elements Test: Earlier diagnosis of the correlation between motor and executive dysfunction in Parkinson's disease without dementia - Murakami, Hidetomo; Owan, Yoshiyuki; Oguchi, Tatsunori; Nomoto, Shohei; Shozawa, Hidenobu; Kubota, Satomi; Mori, Yukiko; Mizuma, Keita; Futamura, Akinori; Kobayakawa, Mutsutaka; Kezuka, Machiko; Midorikawa, Akira; et al. (Neurology and clinical neuroscience, 2015)
Background In patients with Parkinson's disease, executive deficits are known to correlate with motor dysfunctions, such as gait and postural instability. However executive deficits are sometimes difficult to detect using common frontal assessment batteries. Behavioral Assessment of Dysexecutive Syndrome includes six subtests to evaluate different aspects of executive function required in daily life. Among these the Modified Six Elements Test examines higher levels of executive function with regard to prospective memory and organization of behavior. Aim Using Behavioral Assessment of Dysexecutive Syndrome we examined which types of executive dysfunction correlate with motor symptoms in Parkinson's disease without apparent dementia. Methods A total of 54 Parkinson's disease patients with Mini‐Mental State Examination scores over 24 were assessed with the Unified Parkinson's Disease Rating Scale (total score of parts II and III as general motor function, subscores of tremor, rigidity, bradykinesia, gait disturbance and postural instability) for motor assessment, and both the Behavioral Assessment of Dysexecutive Syndrome (total raw score of all subtests and subscores of each of the 6 subtests) and Frontal Assessment Battery for executive function. Correlation coefficients for executive and motor assessments were compared. Results Among the Behavioral Assessment of Dysexecutive Syndrome subtests, the Modified Six Elements Test showed the strongest correlation with the Unified Parkinson's Disease Rating Scale subscore of gait disturbance, but did not correlate with patient background factors, such as age. Conclusion Even in Parkinson's disease without apparent dementia, deficits in complex executive functions, such as prospective memory and organization of behavior, correlate with motor dysfunctions, especially gait. We believe the Modified Six Elements Test is useful to evaluate early executive deficits.